Vitamin D Receptor Agonists Target CXCL10: New Therapeutic Tools for Resolution of Inflammation. (17th April 2013) - Scolletta, Sabino; Colletti, Marta; Di Luigi, Luigi; Crescioli, Clara
Abstract : Understanding the many biological extraskeletal actions of vitamin D has increased in the past decades. Indeed, vitamin D and analogue molecules, besides the classical actions on bone metabolism, exert several beneficial effects on metabolic homeostasis, heart-cardiovascular, brain, and muscle physiological functions, throughout the interaction with the specific vitamin D receptor (VDR). In particular, VDR agonists powerfully control innate and adaptive immune system with favorable effects on human health. VDR ligands act as immunomodulators that are potent enough to retain anti-inflammatory effects, even though the mechanism underlying those effects is not yet fully elucidated. VDR agonists exert a significant suppression of inflammatory processes switching the immune response from T helper 1 (Th1) to T helper 2 (Th2) dominance and counteracting the self-enhancing inflammatory loop between immune and resident cells, especially by cytokine release impairment. Those molecules are able, indeed, to reduce the release of the interferon (IFN)γ -induced 10 kDa protein IP-10/CXCL10, a powerful chemokine driving Th1-mediated inflammation. Based on their features, VDR ligands show the potentiality to be included in immunosuppressive regimens, aimed to control auto- and alloimmune Th1-driven overreactivity, occurring, for example, in autoimmune disease or graft rejection.